Growth, yield and water use efficiency of Indian mustard (Brassica juncea L.) as influenced by irrigation frequency and row spacing - PK Tyagi,; AK Upadhyay, (Journal of Oilseed Brassica, 2026)
Effect of irrigation frequency and row spacing on growth, yield and water use efficiency of Indian mustard[Brassica juncea (L.) Czern & Coss.] cultivar Pusa Tarak was studied at J.N.K.V.V., College of Agriculture,Tikamgarh (Madhya Pradesh), India during two consecutive Rabi seasons of 2012-13 and 2013-14. Theexperiment was laid out in split-plot design with three replications, consisted three irrigation frequencies viz.,I0 (no post sowing irrigation), I1 (one irrigation at 40 DAS) and I2 (two irrigation at 40 and 75 DAS) as mainplot treatments and three row spacing viz., S1 (20 cm), S2 (30 cm) and S3 (40 cm) as sub-plot treatments.Results showed that application of two irrigations at 40 and 75 DAS (I2) resulted into significantly greaterplant height, more number of branches (plant-1), total dry biomass (g plant-1), LAI at 75 DAS, more numberof siliquae (plant-1), number of seeds (siliqua-1), seed yield (kg ha-1), biological yield (kg ha-1) and harvestindex followed by one irrigation (I1) and the lowest under no post sowing irrigation (I0). Irrigation frequencyincreased the consumptive water use (CU) considerably and an increased in CU by application of twoirrigations (I2) and one irrigation (I1) was 33.1% and 8.34%, respectively over no-post sowing irrigation (I0).On the other hand, WUE (kg ha-1-mm) was recorded significantly higher with the application of one irrigations(I1) followed by 2 irrigations (I2) and no-post sowing irrigation ((I0)). WUE between no-post sowing irrigation(I0) and application of 2 irrigations (I2) did not differ significantly. The significantly greater plant height atharvest was observed at closer spacing of 20 cm (S1) followed by 30 cm (S2) and 40 cm (S3). The significantlymore number of branches (plant-1), LAI, dry biomass (g plant-1), number of siliquae (plant-1), number of seeds(siliqua-1) and higher 1000 seed weight (g) were recorded at wider spacing of 40 cm (S3) and these parameterswere the lowest at closest spacing of 20 cm (S1). Similarly, wider spacing of 40 cm (S3), been on par with 30cm (S2) also produced significantly higher seed yield (kg ha-1) and biological yield (kg ha-1) over the closerrow spacing of 20 cm (S1). Harvest index among row spacing did not differ significantly. WUE was realizedsignificantly higher with 40 cm (S3) followed by 30 cm (S2) and 20 cm (S1). However, consumptive water usewas higher with closer row spacing of 20 cm followed by row spacings of 30 cm and 40 cm. Higher accumulationof dry biomass, more number of branches, more number of siliquae and more number of seeds in mustardultimately elevated the seed yield as confirmed by relationship study between seed yield and these parameters.